Urban trees to mitigate microclimate conditions in Goiânia, Goiás - Weirich, Rhayssa Alessandra; Calil, Francine Neves; Monteiro, Marina Morais; Gonçalves, Bruno Bastos; Neto, Carlos De Melo e Silva; Venturoli, Fábio (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
Urban trees can influence from landscape factors to microclimatic, affecting human well-being. This study had as objective to characterize two different sectors in Goiânia, Goiás, Brazil and to verify how urban trees influence the microclimate. Two different areas, 1 km long each one, in two avenues from the city (Goiás Av. and Planície Av.). In each area, a census from all trees was conducted and the following variables were measured: temperature (ºC), relative humidity (%), wind speed (km/h) and light intensity (lux). Descriptive analysis with absolute and relative frequency of tree species, Mann-Whitney (95%) test for comparing abundance among species, T Test (95%) for microclimate variables comparison among full sun and shaded areas in each one of the avenues and the last procedures were a principal components analysis (PCA) and a correspondence analysis (CCA) to verify the influence of environmental variables between full light and shaded areas. In areas shaded by trees crowns, temperatures, light intensity and wind speed showed lower values than shaded areas, while relative humidity showed higher values in these environments than in places without trees. Urban trees contribute to microclimatic conditions improvement in urban landscapes, positively influencing human well-being in urban centers.